Integration of Digital Technology in Learning as A Strategy to Strengthen Student Learning Independence - Nissa, Ismaul Khoirin; Inayati, Nurul Latifatul (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
The development of digital technology has significantly changed the educational landscape and presented new opportunities to strengthen students' learning independence. This article examines the integration of digital technology including Learning Management System (LMS), Massive Open Online Courses (MOOC), artificial intelligence (AI), and collaborative platforms as a strategy to strengthen independent learning and self-regulation. The study uses a descriptive quantitative approach based on a literature review from Scopus indexed journal articles in the period 2022–2025. The search process is carried out through Boolean queries that are relevant to the themes of technology, independence, digital education, and integration, then selected using PRISMA guidelines. Of the 146 articles identified at the initial stage, the application of inclusion criteria (empirical articles, published in journals, relevant to the topic) resulted in 8 articles that were further analyzed. The results of the synthesis show that the integration of digital technology is positively correlated with improved academic performance, motivation, and learning engagement. AI-based technologies, such as chatbots and intelligent tutoring systems, contribute through real-time feedback, adaptive learning paths, and learning personalization that strengthen students' self-regulation skills (planning, monitoring, and reflection). However, the implementation of technology still faces challenges in the form of inequality of access, infrastructure readiness, and educators' digital competence in designing learning that is in line with pedagogical goals. In addition, there is a risk of over-reliance on technology, especially AI, which has the potential to lower deep cognitive engagement and inhibit critical thinking if not accompanied by proper instructional guidance. Therefore, the integration of digital technology needs to be placed as a scaffolding that supports learning autonomy, while at the same time being balanced by strengthening digital literacy, mature instructional design, and developing educator competencies so that the benefits of digital transformation can be optimal and sustainable.